The Analysis on Symbol of Shadowhunter as Seen in Cassandra Clare’s Mortal Instruments - Raflis Raflis; Irwan Syahputra (Fakultas Sastra Universitas Ekasakti, 2020)
This reseacrh aims to determine the main symbols in the novel The Mortal Instruments: City of Bones. It is known that symbols are part of literary works such as poetry, songs, paintings, dramas; a narrative that has a message that the symbol implies. The author also describes and conveys the meaning of each symbol so that the public understands that the symbols used have different meanings from their true meanings. The method used in this research is a qualitative method because this method is suitable for studying the symbols used in the novel. From the research that has been done, the writer found that in The novel, there are several symbols that make the story interesting and have a big impact from the beginning to the end of the story. The author found thirteen main symbols in the story, namely Angelic Power, Soundless, Voyant Sight, Promise, Vision, Speech, Visible, Precision, Heal, Deflect / Block, Speed, Strength, and These thirteen main symbols are interrelated in the story and make the story more interesting.